2019
DOI: 10.1109/access.2019.2892492
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Correlation Aided Ensemble of Classifiers for BCI Oriented EEG Study

Abstract: Recently, Brain-computer interface (BCI) oriented electroencephalographic (EEG) studies have received due attention for decoding human brain signals corresponding to a specific mental state and providing an alternate solution to the disabled or paralyzed persons for communicating with the computer, robotic arm, or various neural prostheses. In this paper, we propose a two-phase approach to distinguish EEG signals of different mental tasks. The first phase combines the cross-correlation features and slow cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…EEG, which is one of these devices, is more preferred than other tools because it is noninvasive, economical, practical, and easy to operate. The accuracy, robustness, and reliability of the EEGrelated methodology combined with deep learning (DL) has proven with many research in brain-computer interface (BCI), especially in motor imagery task classification, [5][6][7][8][9][10][11][12][13] epileptic seizure prediction and detection, [14][15][16][17][18][19][20][21][22][23] drivers fatigue prediction, 24,25 emotion and affective state classification, [26][27][28][29][30][31][32] sleep stage detection, [33][34][35][36] prognosis in rapid eye movement behavior disorder, 37 EEG-based diagnosis of various neurodegenerative diseases, including attention deficit/hyperactivity disorder, 38 schizophrenia, 39,40 Creutzfeldt-Jacob disease, 41 Parkinson's disease, 42 Alzheimer's disease, 43 mild cognitive impairment, 44 predicting transcranial direct current stimulation treatment outcomes of patients with MDD has been studied in the recent literature. 45 The performance of a machine learning methodology based on the pretreatment EEG for MDD pro...…”
Section: Introductionmentioning
confidence: 99%
“…EEG, which is one of these devices, is more preferred than other tools because it is noninvasive, economical, practical, and easy to operate. The accuracy, robustness, and reliability of the EEGrelated methodology combined with deep learning (DL) has proven with many research in brain-computer interface (BCI), especially in motor imagery task classification, [5][6][7][8][9][10][11][12][13] epileptic seizure prediction and detection, [14][15][16][17][18][19][20][21][22][23] drivers fatigue prediction, 24,25 emotion and affective state classification, [26][27][28][29][30][31][32] sleep stage detection, [33][34][35][36] prognosis in rapid eye movement behavior disorder, 37 EEG-based diagnosis of various neurodegenerative diseases, including attention deficit/hyperactivity disorder, 38 schizophrenia, 39,40 Creutzfeldt-Jacob disease, 41 Parkinson's disease, 42 Alzheimer's disease, 43 mild cognitive impairment, 44 predicting transcranial direct current stimulation treatment outcomes of patients with MDD has been studied in the recent literature. 45 The performance of a machine learning methodology based on the pretreatment EEG for MDD pro...…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that brain-computer interfaces (BCIs) may be utilized to evaluate complex states, extending its use into the field of psychology. Paranjape, Dhabu, Deshpande, and Kekre [23] propose a BCI oriented on EEG, which can identify whether a given visual input elicited a favorable or negative emotional response.…”
Section: Complex Computing Robotics Gaming and Miscellaneous Applicat...mentioning
confidence: 99%
“…Aimed to detect the across-subjects discrimination and demonstrate the effectiveness of our method, the results obtained the reference mentioned method CSP-LDA [50], KNN [51], RNN [52], and CNN [53] for decoding the same MI tasks are compared with different training strategy as illustrated in Fig. 11.…”
Section: Model Evaluationmentioning
confidence: 99%